Perfil de adultos iniciantes em aulas individuais de canto na Região Metropolitana de Belo Horizonte - Letícia Muniz dos Santos (2023)
In this dissertation, we examined the profile of adult beginners attending individual singing lessons in the metropolitan region of Belo Horizonte, MG. In Brazil, many people seek singing lessons for the first time as adults, without having had any formal contact with music before, whether during basic education or in specialized schools. The general objective of the study was to get to know these individuals and gain a deeper understanding of their specific characteristics and needs, with a view to better adaptation and the future improvement proposals for the teaching of music and singing. The specific objectives are 1) to identify the socio-economic-cultural characteristics of those individuals, 2) to determine their motivations for seeking singing lessons, 3) to understand the difficulties and potentialities they encounter in that learning process, 4) to comprehend how they relate to music, how they incorporate singing and the study of singing into their life context, and the repertoire they are interested in and 5) to learn about the teachers' evaluations of their students’ musical knowledge and the potential of singing lessons for their overall musical development. A research strategy that combines qualitative and quantitative approaches was adopted, although the primary focus of the investigation was qualitative and exploratory in nature. Data collection involved an electronic questionnaire administered to 20 singing students aged 18 to 65, residing in Belo Horizonte, MG, and the metropolitan area, who had not previously attended formal singing lessons for more than 2 years, as well as 37 singing teachers with students exhibiting these characteristics. Data were collected regarding the socio-economic-cultural characteristics of adult students, their motivations for learning to sing, the difficulties and potentialities encountered in the learning process, and their relationship with music and singing. For teachers, the questions focused on how they perceive the musical knowledge of their adult beginner students, their strengths, and challenges. The results revealed a profile characterized by socio-economic stability, limited ethnic, gender, and sexual diversity, motivations strongly influenced by affection towards music, and a variety of challenges and potentialities in vocal learning, highlighting the importance of customization in lessons It is expected that the findings may contribute to a better understanding of the phenomenon of adult beginners in singing classes and to future research in the fields of Music Education for adults and Vocal Pedagogy, specifically in teaching singing to beginners.